A more thorough analysis of the countermovement jump demonstrates changes in neuromuscular performance during pre and early competitive season in elite futsal players - Spyrou, K.; Alcaraz, P. E.; Marín-Cascales, E.; Cohen, D. D.; Freitas, T. T. (Sport Sciences for Health, 2024)
Purpose This study aimed to investigate the variations on vertical jump and sprint performance during the first weeks of a futsal season.